Boroaluminosilicate glass compositions having high fusion flow rates and advantageous relative forming temperatures
By using boroaluminosilicate glass materials of specific components and high-temperature melt-flow forming technology, the shortcomings of existing glass materials in terms of thermal and mechanical properties are solved, and high-performance, low-density glass plate preparation is achieved.
Patent Information
- Application Number
- JP2024548694
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-09
- Filing Date
- 2023-03-03
- Publication Date
- 2025-04-11
AI Technical Summary
Existing glass materials have shortcomings in thermal and mechanical properties, and are of heavy quality, making it difficult to meet the high-performance needs of automotive and architectural glass.
The glass plates were prepared by high temperature melt-flow forming technology using boroaluminosilicate glass materials containing 55 mol% to 67 mol% SiO2, 10 mol% to 13 mol% B2O3, 11 mol% to 15 mol% Al2O3 and 12 mol% to 16 mol% alkali oxide.
It improves the thermal and mechanical properties of glass materials, reduces density, enhances the forging and compressive resistance of glass, and is suitable for high-performance applications of automotive and architectural glass.
Smart Images

Figure 2025509090000001_ABST
Abstract
Description
Priority
[0001] This application claims the benefit of priority under 35 U.S.C. § 119 of U.S. Provisional Patent Application No. 63 / 318,221, filed March 9, 2022, the contents of which are relied upon and incorporated herein by reference in their entirety. [Technical field]
[0002] The present disclosure relates to glass compositions and glass articles made therefrom, and more particularly to boroaluminosilicate glass compositions that can be fusion formed at relatively high fusion flow rates. [Background technology]
[0003] Glass is used in windows for its optical clarity and durability. Automotive and architectural windows may contain a laminate including one ply of glass or two plies of glass with an interlayer of polymeric material between them. For automotive applications in particular, laminates tend to be used to improve fuel economy and / or crash performance. Some laminate designs may utilize a thicker outer ply of glass and a thinner inner ply of glass. Soda lime glass is often used for both the inner and outer plies because it is readily available in a variety of sizes and thicknesses and is relatively inexpensive. Summary of the Invention [Problem to be solved by the invention]
[0004] However, compared to certain other glass compositions, soda-lime glass is relatively unfavorable in terms of thermal and mechanical properties, and in terms of mass. Thus, there is a need for improved glasses for use as both the thinner inner glass plies and the thicker outer glass plies in laminates. [Means for solving the problem]
[0005] According to one aspect, an embodiment of the present disclosure relates to a glass composition comprising about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides. In one or more embodiments, the glass composition is a glass composition having a viscosity of about 100% at about 630° C. to about 650° C. 11 P.
[0006] In accordance with another aspect, embodiments of the present disclosure relate to a method of forming a glass ply, in which at least two streams of a glass composition overflow a trough in an isopipe. In one or more embodiments, the glass composition includes about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides. The at least two streams of glass composition are fused at a base of the isopipe to form a glass ply according to the method.
[0007] According to yet another aspect, embodiments of the present disclosure relate to a method in which a stack of a first ply of glass and a second ply of glass are placed on a bending ring having an open interior. According to one or more embodiments of the method, the first ply of glass is placed on a bending ring having an open interior, the first ply of glass being oriented such that the viscosity of the first ply of glass is 10 11 The second ply of glass has a first temperature of 10 poise and the second ply of glass has a viscosity of 10 11 The laminate has a second temperature that is poise. In embodiments, the first temperature is different from the second temperature. The laminate is heated to a temperature at which the laminate sags into the open interior of the bending ring. In one or more embodiments, the first glass ply is made from a first glass composition that includes about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides.
[0008] Additional features and advantages are set forth in the following detailed description, and in part will be readily apparent to those skilled in the art from that description, or may be learned by practicing the embodiments as described herein, including the following detailed description, the claims, and the accompanying drawings.
[0009] It is to be understood that both the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. [Brief description of the drawings]
[0010] The accompanying drawings are included to provide a further understanding, and are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiment(s), and together with the description, serve to explain the principles and operation of the various embodiments. [Figure 1] FIG. 1 illustrates a vehicle equipped with a glazing article or laminate according to one or more embodiments. [Diagram 2] FIG. 1 is a side view of a glass article according to one or more embodiments. [Diagram 3] FIG. 1 is a side view of a laminate including a glass article according to one or more embodiments. [Figure 4] FIG. 1 is a side view of a curved laminate including a glass article according to one or more embodiments. [Diagram 5] FIG. 1 illustrates a fusion forming apparatus for fusion forming glass plies of a boroaluminosilicate glass composition, according to an example embodiment. [Figure 6] FIG. 1 illustrates a system with a sensor configured to transmit and receive signals through a glass laminate having at least one glass ply made from a boroaluminosilicate glass composition, according to an example embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Reference will now be made in detail to various embodiments of glass plies and laminates made from boroaluminosilicate glass compositions, examples of which are illustrated in the accompanying drawings, and methods of making the same. Embodiments of the present disclosure relate to boroaluminosilicate glass compositions that can be fusion formed at high mass flow rates. Advantageously, high mass flow rates reduce manufacturing costs. Additionally, the compositions provide glass that is conducive to current anti-forming techniques, such as 10 11 The temperature at which viscosity is in poise (T 11 In an embodiment, the boroaluminosilicate glass composition comprises about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides (one or more of Li2O, K2O, and primarily Na2O). The boroaluminosilicate glass compositions described herein are particularly suitable for laminate applications, such as automotive glazing. More particularly, the boroaluminosilicate glass compositions can be used as the thinner interior facing glass ply of an automotive glazing. These and other aspects and advantages of the disclosed boroaluminosilicate glass compositions are described in more detail below. The embodiments described herein are presented by way of example and not limitation.
[0012] Embodiments for the boroaluminosilicate glass compositions are described herein with respect to a vehicle 100 as shown in FIG. 1. The vehicle 100 includes a body 110 defining an interior and at least one opening 120 communicating with the interior. The vehicle 100 further includes an automotive glazing 130, i.e., a window, disposed within the opening 120. The automotive glazing includes at least one ply of the boroaluminosilicate glass compositions described herein. The automotive glazing 130 may form a side window, a windshield, a rear window, a window, and a sunroof in the vehicle 100. In some embodiments, the automotive glazing 130 may form an interior partition (not shown) in the interior of the vehicle 100, or may be disposed on the exterior of the vehicle 100, forming, for example, an engine block cover, a headlight cover, a taillight cover, a door panel cover, or a pillar cover. As used herein, vehicle includes automobiles (an example of which is shown in FIG. 1), rolling stock, locomotives, boats, ships, aircraft, helicopters, drones, spacecraft, etc. Additionally, although this disclosure is configured with respect to vehicles, the boroaluminosilicate glass compositions may be used in other contexts, such as architectural glazing or bulletproof glazing applications.
[0013] As shown in Figure 2, in embodiments, the automotive glazing 130 includes at least one glass ply 200 that comprises, consists of, or consists essentially of an embodiment of the boroaluminosilicate glass composition described herein. In one or more embodiments, the automotive glazing 130 includes only one glass ply 200 (i.e., a single glass ply is sometimes referred to in the industry as a monolith). As can be seen in Figure 2, the glass ply 200 has a first major surface 202 and a second major surface 204. The first major surface 202 is opposite the second major surface 204. A minor surface 206 extends around the periphery of the glass ply 200 and connects the first major surface 202 and the second major surface 204.
[0014] A first thickness 210 is defined between the first major surface 202 and the second major surface 204. In embodiments, the first thickness 210 is from about 0.1 mm to about 2.0 mm, specifically, from about 0.3 mm to about 1.5 mm, and most specifically, from about 0.5 mm to about 1.1 mm.
[0015] In some embodiments, the glass ply may have a rounded or tubular curvature, such as when the first major surface is the exterior and the second major surface is the interior surface of a tube. In some embodiments, the perimeter of the glass ply is generally straight, while in other embodiments, the perimeter is complex. The first major surface may have openings, slots, holes, protrusions, depressions, or other shapes.
[0016] FIG. 3 illustrates an embodiment of an automotive glazing 130 where the automotive glazing 130 is a laminate structure 300 including the glass ply 200 of FIG. 2 as a first glass ply 310. As previously mentioned, the glass ply 200 can include, consist of, or consist essentially of an embodiment of the boroaluminosilicate glass composition described herein. In the embodiment illustrated in FIG. 3, the first glass ply 310 is joined to the second glass ply 320 by an interlayer 330. Specifically, the second glass ply 320 has a third major surface 332 and a fourth major surface 334. The third major surface 332 is opposite the fourth major surface 334. A minor surface 336 extends around the periphery of the second glass ply 320 and connects the third major surface 332 and the fourth major surface 334.
[0017] A second thickness 340 is defined between the third major surface 332 and the fourth major surface 334. In embodiments, the second thickness 340 is greater than the first thickness 210 of the first ply of glass 310. In embodiments, the second thickness is greater than 2 mm. In embodiments, the total glass thickness (i.e., the first thickness 210 plus the second thickness 340) is 8 mm or less, 7 mm or less, 6.5 mm or less, 6 mm or less, 5.5 mm or less, or 5 mm or less. In embodiments, the lower limit of the total glass thickness is about 2 mm.
[0018] In an embodiment, the second ply of glass 320 is made from a glass composition that is different than the boroaluminosilicate glass composition of the first ply of glass 310. In an embodiment, the second glass composition comprises a soda-lime silicate composition or a borosilicate glass composition (e.g., a fusion-formable borosilicate glass composition comprising 74 mol% to 80 mol% SiO2, 2.5 mol% to 5 mol% Al2O3, 11.5 mol% to 14.5 mol% B2O3, 4.5 mol% to 8 mol% Na2O, 0.5 mol% to 3 mol% K2O, 0.5 mol% to 2.5 mol% MgO, and 0 mol% to 4 mol% CaO, among others). The second glass ply 320 may be formed from any of the borosilicate glass compositions described in International Patent Application No. US2021 / 61966, filed December 6, 2021, entitled “Glass with Unique Fracture Behavior for Vehicle Windshield,” which is incorporated herein by reference in its entirety. In an embodiment, the second ply of glass 320 has a concentration that satisfies the relationships: (relationship 1) SiO2≧72 mol%, e.g., SiO2≧72.0, e.g., SiO2≧73.0, e.g., SiO2≧74.0, and / or SiO2≦92, e.g., SiO2≦90; (relationship 2) B2O3≧10 mol%, e.g., B2O3≧10.0, e.g., B2O3≧10.5, and / or B2O3≦20, e.g., B2O3≦18; (relationship 3) (R2O+R'O)≧Al2O3, e.g., (R2O+R'O)≧(Al2O3+1), (R2O+R'O)≧(Al2O3+2); and and / or (relationship 4): 0.80≦(1−[(2R2O+2R′O) / (SiO2+2Al2O3+2B2O3)])≦0.93, where R2O is the sum of the concentrations of one or more alkali metal oxides and, if included in a borosilicate glass composition, R′O is the sum of the concentrations of one or more divalent cation oxides.R2O may be, for example, the sum of Li2O, Na2O, K2O, Rb2O, and Cs2O, and R'O may be, for example, the sum of MgO, CaO, SrO, BaO, and ZnO.
[0019] In embodiments, the glass composition of second glass ply 320 may include Al2O3 and Na2O in amounts that satisfy the relationship Na2O>Al2O3+1 (e.g., Na2O>Al2O3+1.25, Na2O>Al2O3+1.5, Na2O>Al2O3+1.75, Na2O>Al2O3+2.0). In embodiments, the Al2O3 content of the glass composition of second glass ply 320 is 2.0 mol% or more and 5.0 mol% or less (e.g., 2.5 mol% or more and 5.0 mol% or less, 3.0 mol% or less and 5 mol% or less). When the composition of the second glass ply 320 has 12.0 mol% or more B2O3 (e.g., 13.0 mol% or more B2O3, 14.0 mol% or more B2O3, 15.0 mol% or more B2O3, and 16.0 mol% or less B2O3), such Al2O3 content is sufficient to prevent phase separation of the borosilicate glass, yet low enough that SiO2 and B2O3 are the primary glass formers in the glass. With Al2O3 content at such levels, the Na2O content over Al2O3 assists in dissolving silica during melting of the glass. In an embodiment, the Na2O content in the glass composition of the second glass ply 320 is 6.25 mol% or less (e.g., 6.20 mol% or less, 6.15 mol% or less, 6.10 mol% or less, 6.05 mol% or less, 6.0 mol% or less). In some embodiments, the Na2O content is at least 4.0 mol%. In some embodiments, if the Na2O content of the second glass ply 320 meets these criteria, K2O, if included, is present in an amount less than Na2O, such as an amount less than or equal to 0.8 mol% and less than or equal to 5 mol%, since K2O tends to increase the CTE to a greater extent than Na2O per unit of composition. For example, in some embodiments, the glass composition of the second glass ply 320 may include a ratio of K2O to Na2O of about 0.1 to about 0.75. Glass compositions that meet the above constraints may be suitable for fusion forming, exhibit the unique fracture behavior described herein, and still have a desirably low CTE.
[0020] Additionally, in embodiments, the first ply of glass 310 and / or the second ply of glass 320 may be strengthened. For example, the first ply of glass 310 and / or the second ply of glass 320 may be thermally, chemically, and / or mechanically strengthened. Specifically, in embodiments, the first ply of glass 310 and / or the second ply of glass 320 may be chemically strengthened by an ion exchange process. In one or more embodiments, the first ply of glass 310 and / or the second ply of glass 320 may be mechanically strengthened by taking advantage of the mismatch in thermal expansion coefficients between portions of the plies to create areas of compressive stress and a central region that exhibits tensile stress. In some embodiments, the first ply of glass 310 and / or the second ply of glass 320 may be thermally strengthened by heating the plies to a temperature above their glass transition temperature and then quenching. In some embodiments, various combinations of chemical, mechanical, and thermal strengthening may be used to strengthen the first ply of glass 310. In one or more embodiments, the first ply of glass 310 is tempered while the second ply of glass 320 is untempered (but may be annealed, if desired) and exhibits a surface compressive stress of less than about 3 MPa, or about 2.5 MPa or less, 2 MPa or less, 1.5 MPa or less, 1 MPa or less, or about 0.5 MPa or less.
[0021] In one or more embodiments, an interlayer 330 bonds the second major surface 204 of the first glass ply 310 to the third major surface 332 of the second glass ply 320. In embodiments, the interlayer 330 is made from a polymer such as polyvinyl butyral (PVB), acoustic PVB (APVB), ionomer, ethylene vinyl acetate (EVA), and at least one of thermoplastic polyurethane (TPU), polyester (PE), polyethylene terephthalate (PET), and the like. The thickness of the interlayer may range from about 0.5 mm to about 2.5 mm, particularly about 0.7 mm to about 1.5 mm. In other embodiments, the thickness may be less than 0.5 mm or greater than 2.5 mm. Additionally, in embodiments, the interlayer 330 may include multiple polymer layers or films that provide various functionalities to the laminate structure 300. For example, the interlayer 330 may incorporate at least one of display features, solar insulation, sound deadening, antennas, anti-glare treatments, or anti-reflective treatments, among others. In particular embodiments, the interlayer 330 is modified to provide ultraviolet (UV) absorption, infrared (IR) absorption, IR reflection, acoustic control / attenuation, adhesion promotion, and color tint. The interlayer 330 may be modified with suitable additives, such as dyes, pigments, dopants, and the like, to impart desired properties.
[0022] In one or more embodiments, the first ply of glass 310 or the second ply of glass 320 may be provided with a functional or decorative coating in addition to or in place of the functional or decorative film of the interlayer 330. In embodiments, the coating is at least one of an infrared reflective (IRR) coating, a frit, an anti-reflective coating, or a pigmented coating. In an exemplary embodiment of an IRR, the second major surface 204 of the first ply of glass 310 or the third major surface 332 of the second ply of glass 320 is coated with an infrared reflective film and, optionally, one or more layers of a transparent dielectric film. In embodiments, the infrared reflective film is made from a highly conductive metal, such as silver, gold, or copper, which reduces the transfer of heat through the coated plies 310, 320. In embodiments, an optional dielectric film can be used to prevent reflection of the infrared reflective film and to control other properties and characteristics of the coating, such as color and durability. In embodiments, the dielectric film is made from one or more oxides of zinc, tin, indium, bismuth, and titanium, among others. In an exemplary embodiment, the IRR coating includes one or two silver layers, each sandwiched between two layers of transparent dielectric film. In embodiments, the IRR coating is applied, for example, using physical or chemical vapor deposition, or by lamination.
[0023] In embodiments, one or both of the first ply of glass 310 and the second ply of glass 320 include a frit. In embodiments, the frit is applied, for example, to the first major surface 202 of the first ply of glass 310, the second major surface 204 of the first ply of glass 310, and / or the third major surface 332 of the second ply of glass 320. In embodiments, the frit provides an improved bonding surface for an adhesive, such as an adhesive that bonds the glass sheet to the interlayer 330 or to the bonding surface that defines the opening 120 of the vehicle body 110. Additionally, in embodiments, the frit provides a decorative border for the glass sheet 130. Furthermore, in embodiments, the frit may be used in addition to the IRR coating described above. In embodiments, the frit is an enamel frit. In other embodiments, the frit is designed to be ion-exchangeable. That is, the frit may be applied to an ion-exchangeable glass (such as the presently disclosed boroaluminosilicate glass composition) prior to undergoing an ion-exchange process. Such frits are made to allow for the exchange of ions between the glass and the treatment bath. In embodiments, the frits are Bi-Si-B alkaline, Zn-based Bi-based, Bi-Zn based, Bi-based, Bi-low or no Bi Si-Zn-B-Ti based, Si-Bi-Zn-B-alkali, and / or Si-Bi-Ti-B-Zn-alkali, among others. An example of an ion-exchangeable frit containing colorants is 45.11 mol% Bi2O3, 20.61 mol% SiO2, 13.56 mol% Cr2O3, 5.11 mol% CuO, 3.48 mol% MnO, 3.07 mol% ZnO, 2.35 mol% B2O3, 1.68 mol% TiO2, 1.60 mol% Na2O, 1.50 mol% Li2O, 0.91 mol% Cr2O3, 0.11 mol% CuO, 0.11 mol% MnO, 0.11 mol% Li2O, 0.11 mol% Na2 ... % K2O, 0.51 mol% Al2O3, 0.15 mol% P2O5, 0.079 mol% SO3, 0.076 mol% BaO, 0.062 mol% ZrO2, 0.060 mol% Fe2O3, 0.044 mol% MoO3, 0.048 mol% CaO, 0.018 mol% Nb2O5, 0.006 mol% Cl, and 0.012 mol% SrO.Other examples of ion-exchangeable frits are disclosed in U.S. Pat. No. 9,346,708 B2 (Application No. 13 / 464493, filed May 4, 2012), and U.S. Patent Application Publication No. 2016 / 0002104 A1 (Application No. 14 / 768832, filed August 19, 2015), both of which are hereby incorporated by reference in their entireties.
[0024] In an embodiment, the first ply of glass 310 may be provided with a colorant coating comprising an ink, such as an organic ink. In an embodiment particularly suited for such a colorant coating, the colorant coating is applied to the first major surface 202 of the first ply of glass 310 or the second major surface 204 of the first ply of glass 310, and the first ply of glass 310 is cold formed against the second ply of glass 320. Advantageously, such a colorant coating can be applied to the first ply of glass 310 while the first ply of glass 310 is in a planar configuration, and the first ply of glass 310 can then be cold formed into a curved configuration without destroying the colorant coating, e.g., the organic ink coating. In an embodiment, the colorant coating comprises at least one pigment, at least one inorganic filler, and a binder comprising an alkoxysilane-functionalized isocyanurate or an alkoxysilane-functionalized biuret. Examples of such colorant coatings are described in EP 2 617 690 B1, which is incorporated herein by reference in its entirety. Other suitable colorant coatings and methods of applying the colorant coatings are described in U.S. Patent Application Publication No. 2020 / 0171800A1 (Application No. 16 / 613010, filed November 12, 2019), and U.S. Patent No. 9,724,727 (Application No. 14 / 618398, filed February 10, 2015), both of which are hereby incorporated by reference in their entireties.
[0025] In an embodiment, the coating is an anti-reflective coating. In a particular embodiment, the anti-reflective coating is applied to the first major surface 202 of the first ply of glass 310. In an embodiment, the anti-reflective coating comprises multiple layers of low and high refractive index materials, or low, medium and high refractive index materials. For example, in an embodiment, the anti-reflective coating comprises 2 to 13 layers of alternating low and high refractive index materials, such as silica (low refractive index) and niobia (high refractive index). In another exemplary embodiment, the anti-reflective coating comprises 3 to 12 layers of alternating low, medium and high refractive index materials, such as silica (low refractive index), alumina (medium refractive index), and niobia (high refractive index). In yet another embodiment, the low refractive index material in the stack may be an ultra-low refractive index material, such as magnesium fluoride or porous silica. In general, an anti-reflective coating with more layers in the stack will perform better at larger angles of incidence than an anti-reflective coating with fewer layers in the stack. For example, at angles of incidence greater than 60°, an antireflective coating stack having four layers will perform better (less reflective) than an antireflective coating stack having two layers. Additionally, in embodiments, an antireflective coating stack having an ultra-low refractive index material will perform better (less reflective) than an antireflective coating stack having a low refractive index material. Other antireflective coatings known in the art may also be suitable for application to laminate 300.
[0026] In embodiments, the glass ply 200 or laminate 300 exhibits at least one curvature along at least a first axis with a radius of curvature ranging from 300 mm to about 10 m. In embodiments, the glass ply 200 or laminate 300 exhibits at least one curvature along a second axis transverse to, and in particular perpendicular to, the first axis with a radius of curvature ranging from 300 mm to about 10 m. In other embodiments, the glass ply exhibits a curvature, but the curvature has a radius of curvature less than 300 mm or greater than 10 m. In some embodiments, the curvature is complex and varying.
[0027] In embodiments, the curvature is introduced into the glass ply 200 or each glass ply 310, 320 of the glass laminate 300 by a thermal process. The thermal process may include a sagging process that uses gravity to shape the glass ply 200 or glass ply 310, 320 when heated. In a sagging process, a glass ply, such as glass ply 200, is placed on a mold having an open interior, heated in a furnace (e.g., a box furnace, or a glass annealing furnace), and allowed to gradually sag into the open interior of the mold under the influence of gravity. In one or more embodiments, the thermal process may include a pressing process that uses a mold to shape the glass ply 200 or glass ply 310, 320 when or while it is heated. In some embodiments, two glass plies, such as glass plies 310, 320, are molded together in a "pair-molding" process. In such a process, one glass ply is placed on top of another glass ply to form a laminate (which may also include an intervening peel layer), which is placed in a mold. In an embodiment, to facilitate the co-forming process, the glass plies 310 used as the inner and / or thinner glass plies have a higher co-forming temperature (10° C.) than the outer and / or thicker glass plies 320. 11 Temperature in poise, i.e., T 11 For example, in an embodiment, the inner thinner glass ply 310 of the presently disclosed boroaluminosilicate glass composition has a T in the range of 630° C. to 650° C. 11 and the outer thicker glass ply 320 has a T in the range of about 600° C. to about 610° C. for soda-lime silicate glass, or about 605° C. to 640° C. (e.g., 605° C. to 625° C.) for fusion-formable borosilicate glass compositions. 11 Has temperature.
[0028] In one or more embodiments, the mold may have an open interior for use in the sagging process. Both the laminate and mold are heated by placing them in a furnace, and the laminate is gradually heated to the bending or sagging temperature of the glass plies. During this process, the plies are formed together into a curved shape. The T between the inner thinner glass ply 310 and the outer thicker glass ply 320 is 11 Due to the temperature difference, optical distortions that would otherwise occur during pair molding are significantly reduced or eliminated.
[0029] According to an exemplary embodiment, the time and temperature of heating is selected to obtain the desired degree of curvature and final shape. The one or two glass plies are then removed from the oven and cooled. For paired formed glass plies, the two glass plies are separated and reassembled with an interlayer, such as interlayer 330, disposed between the glass plies, and heated, e.g., under vacuum, to seal the glass plies and interlayer together into a laminate.
[0030] In one or more embodiments, only one of the glass plies is curved using heat (e.g., by a sagging or pressing process) and the other glass ply is curved using a cold forming process by pressing the glass ply at a temperature below the softening temperature of the glass composition (specifically, at a temperature below 200° C., below 100° C., below 50° C., or at room temperature) to curve it to match the already curved glass ply. The pressure to cold form the glass ply to the other glass ply may be applied by, for example, a vacuum, a mechanical press, or one or more clamps. The cold formed glass ply may be held in conformity with the curved glass ply by an interlayer and / or by being mechanically fastened or otherwise bonded thereto.
[0031] Figure 4 illustrates an exemplary embodiment of a curved glass laminate 400. As can be seen in Figure 4, the first major surface 202 of the first ply of glass 310 has a first depth of curvature 410, defined as the maximum depth from the plane of the first major surface 202 (dashed line). In embodiments in which the second ply of glass 320 is curved, the third major surface 332 of the second ply of glass 320 has a second depth of curvature 420, defined as the maximum depth from the plane of the third major surface 332 (dashed line).
[0032] In an embodiment, one or both of the first curvature depth 410 and the second curvature depth 420 are greater than or equal to about 2 mm. The depth of curvature may be defined as the maximum distance that a surface is perpendicularly away from a plane defined by points on the circumference of the surface. For example, one or both of the first curvature depth 410 and the second curvature depth 420 may be in a range of about 2 mm to about 30 mm. In an embodiment, the first curvature depth 410 and the second curvature depth 420 are substantially equal to each other. In one or more embodiments, the first curvature depth 410 is within 10% of the second curvature depth 420, and in particular, within 5% of the second curvature depth 420. For illustrative purposes, the second curvature depth 420 may be about 15 mm, and the first curvature depth 410 may be in a range of about 13.5 mm to about 16.5 mm (or within 10% of the second curvature depth 420).
[0033] In one or more embodiments, the first curved glass ply 310 and the second curved glass ply 320 have a shape deviation between the first curved glass ply 310 and the second curved glass ply 320 of ±5 mm or less as measured with an optical three-dimensional scanner, such as an ATOS Triple Scan supplied by GOM GmbH of Braunschweig, Germany. In one or more embodiments, the shape deviation is measured between the second major surface 204 and the third major surface 332 or between the first major surface 202 and the fourth major surface 334. In one or more embodiments, the shape deviation between the first curved glass ply 310 and the second curved glass ply 320 is about ±4 mm or less, about ±3 mm or less, about ±2 mm or less, about ±1 mm or less, about ±0.8 mm or less, about ±0.6 mm or less, about ±0.5 mm or less, about ±0.4 mm or less, about ±0.3 mm or less, about ±0.2 mm or less, or about ±0.1 mm or less. As used herein, shape deviation applies to the laminated glass plies (i.e., not including interlayers) and refers to the maximum deviation from a desired curvature between the aligned positions of the respective second major surface 204 and third major surface 332, or first major surface 202 and fourth major surface 334.
[0034] In one or more embodiments, one or both of the first major surface 202 and the fourth major surface 334 exhibit minimal optical distortion. For example, one or both of the first major surface 202 and the fourth major surface 334 exhibit less than about 400 millidiopters, less than about 300 millidiopters, less than about 250 millidiopters, or less than about 200 millidiopters, as measured with an optical distortion detector using transmission optics. A suitable optical distortion detector is supplied by ISRA VISIION AG, Darmstadt, Germany under the trade name SCREENSCAN-Faultfinder. In one or more embodiments, one or both of the first major surface 202 and the fourth major surface 334 exhibits about 190 millidiopters or less, about 180 millidiopters or less, about 170 millidiopters or less, about 160 millidiopters or less, about 150 millidiopters or less, about 140 millidiopters or less, about 130 millidiopters or less, about 120 millidiopters or less, about 110 millidiopters or less, about 100 millidiopters or less, about 90 millidiopters or less, about 80 millidiopters or less, about 70 millidiopters or less, about 60 millidiopters or less, or about 50 millidiopters or less. As used herein, optical distortion refers to the maximum optical distortion measured at the respective surface.
[0035] In one or more embodiments, the first major surface 202 or the second major surface 204 of the first curved glass ply 310 exhibits low membrane tensile stress. Membrane tensile stress may arise during cooling of the curved plies and laminates. As the glass cools, the major surfaces and edge surfaces (perpendicular to the major surfaces) may develop surface compression that is balanced by the central region exhibiting tensile stress. Such stress may, under some circumstances, be problematic at the periphery where edge cooling effects create stress and bending tools create temperature gradients that cause stress. The low CTE (e.g., 8 ppm / °C or less, 7.8 ppm / °C or less, or 7.5 ppm / °C or less) associated with embodiments of the presently disclosed boroaluminosilicate glass compositions minimizes adverse residual stresses that may arise during the annealing step of hot forming. Such stresses are proportional to the CTE, and therefore, by reducing the CTE of the boroaluminosilicate glass composition, the residual stresses are also reduced.
[0036] Bending or forming may introduce additional surface tension near the edges, moving the central tension region closer to the glass surface. Thus, the membrane tensile stress is the tensile stress measured near the edge (e.g., about 10-25 mm from the edge face). In one or more embodiments, the membrane tensile stress of the first or second major surface of the first curved glass ply is less than about 7 megapascals (MPa) as measured with an edge stress meter according to ASTM C1279. Examples of such surface stress meters include an Edge Stress Meter or VRP (both commercially available from Strainoptic Technologies). In one or more embodiments, the membrane tensile stress of the first or second major surface of the first curved glass ply is less than about 6 MPa, less than about 5 MPa, less than about 4 MPa, or less than about 3 MPa. In one or more embodiments, the lower limit of the membrane tensile stress is about 0.01 MPa or about 0.1 MPa. In other embodiments, the membrane tensile stress can be negligible (e.g., about 0). As discussed herein, stresses are specified as either compressive or tensile, and the magnitude of such stresses is given as an absolute value.
[0037] In one or more embodiments, the laminate 300, 400 can have a thickness of 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, or 6 mm or less, which thickness is the sum of the thicknesses of the first ply of glass 310, the second ply of glass 320, and the interlayer 330. In various embodiments, the laminate 300, 400 can have a thickness in the range of about 1.8 mm to about 10 mm, or in the range of about 1.8 mm to about 9 mm, or in the range of about 1.8 mm to about 8 mm, or in the range of about 1.8 mm to about 7 mm, or in the range of about 1.8 mm to about 6 mm, or in the range of about 1.8 mm to about 5 mm. 2.1 mm to about 10 mm, or about 2.1 mm to about 9 mm, or about 2.1 mm to about 8 mm, or about 2.1 mm to about 7 mm, or about 2.1 mm to about 6 mm, or about 2.1 mm to about 5 mm, or about 2.4 mm to about 10 mm, or about 2.4 mm to about 9 mm, or about 2.4 mm to about 8 mm, or about 2.4 mm to about 7 mm, or about 2.4 mm to about 6 mm, or about 2.4 mm to about 5 mm, or about 3.4 mm to about 10 mm, or about 3.4 mm to about 9 mm, or about 3.4 mm to about 8 mm, or about 3.4 mm to about 7 mm, or about 3.4 mm to about 6 mm, or about 3.4 mm to about 5 mm. In other embodiments, the thickness of the laminate may be less than 1.8 mm or greater than 10 mm.
[0038] In one or more embodiments, the first curved glass ply (or the first glass ply used to form the first curved glass ply) is relatively thin compared to the second curved glass ply (or the second glass ply used to form the second curved glass ply). In other words, the second curved glass ply (or the second glass ply used to form the second curved glass ply) has a greater thickness than the first curved glass ply (or the first glass ply used to form the first curved glass ply). In one or more embodiments, the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) is greater than twice the first thickness. In one or more embodiments, the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) is about 1.5 to about 10 times the first thickness (e.g., about 1.75 to about 10 times, about 2 to about 10 times, about 2.25 to about 10 times, about 2.5 to about 10 times, about 2.75 to about 10 times, about 3 to about 10 times, about 3.25 to about 10 times, about 3.5 to about 10 times, about 3.7 5 to about 10 times, about 4 to about 10 times, about 1.5 to about 9 times, about 1.5 to about 8 times, about 1.5 to about 7.5 times, about 1.5 to about 7 times, about 1.5 to about 6.5 times, about 1.5 to about 6 times, about 1.5 to about 5.5 times, about 1.5 to about 5 times, about 1.5 to about 4.5 times, about 1.5 to about 4 times, about 1.5 to about 3.5 times, about 2 to about 7 times, about 2.5 to about 6 times, about 3 to about 6 times). In other embodiments, the plies may be of other sizes, such as a first ply that is thicker than or the same thickness as a second ply.
[0039] In one or more embodiments, the first thickness (or the thickness of the first ply of glass used to form the first curved ply of glass) is less than 2.0 mm (e.g., 1.95 mm or less, 1.9 mm or less, 1.85 mm or less, 1.8 mm or less, 1.75 mm or less, 1.7 mm or less, 1.65 mm or less, 1.6 mm or less, 1.55 mm or less, 1.5 mm or less, 1.45 mm or less, 1.4 mm or less, 1.35 mm or less, 1.3 mm or less, 1.25 mm or less, 1.2 mm or less, 1.15 mm or less, 1.1 mm or less, 1.05 mm or less, 1 mm or less, 0.95 mm or less, 0.9 mm or less, 0.85 mm or less, 0.8 mm or less, 0.75 mm or less, 0.7 mm or less, 0.65 mm or less, 0.6 mm or less, 0.55 mm or less, 0.5 mm or less, 0.45 mm or less, 0. The first thickness (or the thickness of the first ply of glass used to form the first curved ply of glass) is about 0.1 mm to less than about 2.0 mm, about 0.1 mm to about 1.9 mm, about 0.1 mm to about 1.8 mm, about 0.1 mm to about 1.7 mm, about 0.1 mm to about 1.6 mm, about 0.1 mm to about 1.5 mm, about 0.1 mm to about 1.4 mm, about 0.1 mm to about 1.3 mm, about 0.1 mm to about 1.2 mm, about 0.1 mm to about 1.1 mm, about In the range of 0.1 mm to about 1 mm, about 0.1 mm to about 0.9 mm, about 0.1 mm to about 0.8 mm, about 0.1 mm to about 0.7 mm, about 0.2 mm to less than about 2.0 mm, about 0.3 mm to less than about 2.0 mm, about 0.4 mm to less than about 2.0 mm, about 0.5 mm to less than about 2.0 mm, about 0.6 mm to less than about 2.0 mm, about 0.7 mm to less than about 2.0 mm, about 0.8 mm to less than about 2.0 mm, about 0.9 mm to less than about 2.0 mm, or about 1.0 mm to about 2.0 mm.In other embodiments, the second ply can be thicker than 2.0 mm or thinner than 0.1 mm, such as less than 700 μm, less than 500 μm, less than 300 μm, less than 200 μm, less than 100 μm, less than 80 μm, less than 40 μm, and / or at least 10 μm.
[0040] In some embodiments, the second thickness (or the thickness of the second ply of glass used to form the second curved ply of glass) is greater than or equal to about 2.0 mm. For example, the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) is about 2.0 mm or more, about 2.1 mm or more, about 2.2 mm or more, about 2.3 mm or more, about 2.4 mm or more, about 2.5 mm or more, about 2.6 mm or more, about 2.7 mm or more, about 2.8 mm or more, about 2.9 mm or more, about 3.0 mm or more, about 3.1 mm or more, about 3.2 mm or more, about 3.3 mm or more, 3.4 mm or more, 3.5 mm or more, 3.6 mm or more, 3.7 mm or more, 3.8 mm or more, 3.9 mm or more, 4 mm or more, 4.2 mm or more, 4.4 mm or more, 4.6 mm or more, 4.8 mm or more, 5 mm or more, 5.2 mm or more, 5.4 mm or more, 5.6 mm or more, 5.8 mm or more, or 6 mm or more. In some embodiments, the second thickness (or the thickness of the second glass ply used to form the second curved glass ply) is from about 2.0 mm to about 6 mm, from about 2.1 mm to about 6 mm, from about 2.2 mm to about 6 mm, from about 2.3 mm to about 6 mm, from about 2.4 mm to about 6 mm, from about 2.5 mm to about 6 mm, from about 2.6 mm to about 6 mm, from about 2.8 mm to about 6 mm, from about 3 mm to about 6 mm, from about 3.2 mm to about 6 mm, from about 3.4 mm to about 6 mm, from about 3.6 mm to about 6 mm, from about 3.8 mm to about 6 mm, from about 4 mm to about 6 mm, from about In some embodiments, the diameter of the slit is in the range of about 2.0 mm to about 5.8 mm, about 2.0 mm to about 5.6 mm, about 2.0 mm to about 5.5 mm, about 2.0 mm to about 5.4 mm, about 2.0 mm to about 5.2 mm, about 2.0 mm to about 5 mm, about 2.0 mm to about 4.8 mm, about 2.0 mm to about 4.6 mm, about 2.0 mm to about 4.4 mm, about 2.0 mm to about 4.2 mm, about 2.0 mm to about 4 mm, about 2.0 mm to about 3.8 mm, about 2.0 mm to about 3.6 mm, about 2.0 mm to about 3.4 mm, about 2.0 mm to about 3.2 mm, or about 2.0 mm to about 3 mm.In other embodiments, the second ply can be thicker than about 10.0 mm, or thinner than 2.0 mm, such as less than 1.5 mm, less than 1.0 mm, less than 700 μm, less than 500 μm, less than 300 μm, less than 200 μm, less than 100 μm, less than 80 μm, less than 40 μm, and / or at least 10 μm.
[0041] In one or more specific examples, the second thickness (or the thickness of the second ply of glass used to form the second curved ply of glass) is from about 2.0 mm to about 3.8 mm and the first thickness (or the thickness of the first ply of glass used to form the first curved ply of glass) is in the range of from about 0.1 mm to about 2.0 mm. In embodiments, the ratio of the second thickness to the total glass thickness is at least 0.7, or at least 0.75, or at least 0.8, or at least 0.85, or at least 0.9.
[0042] In one or more embodiments, the laminate 300, 400 is substantially free of visual distortion as measured by ASTM C1652 / C1652M. In particular embodiments, the laminate, the first curved glass ply, and / or the second curved glass ply are substantially free of wrinkles or distortions visually detectable by the naked eye according to ASTM C1652 / C1652M.
[0043] In one or more embodiments, the first major surface 202 or the second major surface 204 has a surface compressive stress of less than 3 MPa as measured by a surface stress meter, such as a surface stress meter ("FSM") commercially available from Orihara Seisakusho Co., Ltd. (Japan) under the trade name FSM-6000. In some embodiments, the first curved glass ply is unstrengthened (but may be annealed, if desired) and exhibits a surface compressive stress of less than about 3 MPa, or about 2.5 MPa or less, 2 MPa or less, 1.5 MPa or less, 1 MPa or less, or about 0.5 MPa or less. In some embodiments, such surface compressive stress ranges are present on both the first major surface and the second major surface.
[0044] In one or more embodiments, the first and second glass plies used to form the first and second curved glass plies are substantially planar prior to being paired to form the first and second curved glass plies. In some cases, one or both of the first and second glass plies used to form the first and second curved glass plies may not exhibit the desired depth of curvature and may have a 3D or 2.5D shape that is ultimately formed during the pairing process and present in the resulting laminate. Additionally or alternatively, the thickness of one or both of the first curved glass ply (or the first glass ply used to form the first curved glass ply) and the second curved glass ply (or the second glass ply used to form the second curved glass ply) may be constant along one or more dimensions or may vary along one or more of its dimensions for aesthetic and / or functional reasons. For example, the edges of one or both of the first curved glass ply (or the first ply of glass used to form the first curved glass ply) and the second curved glass ply (or the second ply of glass used to form the second curved glass ply) may be thicker as compared to more central regions of the glass plies.
[0045] The dimensions of the length (e.g., the longest centerline of a surface (e.g., a first major surface)), width (e.g., the longest dimension of the surface perpendicular to the length), and thickness (e.g., the dimensions of the ply perpendicular to the length and width) of the first curved glass ply (or the first glass ply used to form the first curved glass ply) and the second curved glass ply (or the second glass ply used to form the second curved glass ply) may also vary depending on the application or use of the article. In one or more embodiments, the first curved glass ply (or the first glass ply used to form the first curved glass ply) includes a first length and a first width (the first thickness is perpendicular to both the first length and the first width), and the second curved glass ply (or the second glass ply used to form the second curved glass ply) includes a second length and a second width perpendicular to the second length (the second thickness is perpendicular to both the second length and the second width). In one or more embodiments, either or both of the first length and the first width are greater than or equal to about 0.25 meters (m). For example, the first length and / or the second length can be in the range of about 1 m to about 3 m, about 1.2 m to about 3 m, about 1.4 m to about 3 m, about 1.5 m to about 3 m, about 1.6 m to about 3 m, about 1.8 m to about 3 m, about 2 m to about 3 m, about 1 m to about 2.8 m, about 1 m to about 2.8 m, about 1 m to about 2.8 m, about 1 m to about 2.8 m, about 1 m to about 2.6 m, about 1 m to about 2.5 m, about 1 m to about 2.4 m, about 1 m to about 2.2 m, about 1 m to about 2 m, about 1 m to about 1.8 m, about 1 m to about 1.6 m, about 1 m to about 1.5 m, about 1.2 m to about 1.8 m, or about 1.4 m to about 1.6 m. In some embodiments, the surface dimension from perimeter to perimeter through the center of gravity of each surface (e.g., first surface, second surface, monolith major surface, ply surface) is at least 1 mm, at least 1 cm, at least 10 cm, at least 1 m, and / or no more than 10 m, such that the respective plies will not fail due to inclusion fracture. In other embodiments, the plies may be other sizes.
[0046] For example, the first width and / or the second width can be in the range of about 0.5 m to about 2 m, about 0.6 m to about 2 m, about 0.8 m to about 2 m, about 1 m to about 2 m, about 1.2 m to about 2 m, about 1.4 m to about 2 m, about 1.5 m to about 2 m, about 0.5 m to about 1.8 m, about 0.5 m to about 1.6 m, about 0.5 m to about 1.5 m, about 0.5 m to about 1.4 m, about 0.5 m to about 1.2 m, about 0.5 m to about 1 m, about 0.5 m to about 0.8 m, about 0.75 m to about 1.5 m, about 0.75 m to about 1.25 m, or about 0.8 m to about 1.2 m. In other embodiments, the plies can be other sizes.
[0047] In one or more embodiments, the second length is within 5% of the first length (e.g., about 5% or less, about 4% or less, about 3% or less, or about 2% or less). For example, if the first length is 1.5 m, the second length would be in the range of about 1.425 m to about 1.575 m and still be within 5% of the first length. In one or more embodiments, the second width is within 5% of the first width (e.g., about 5% or less, about 4% or less, about 3% or less, or about 2% or less). For example, if the first width is 1 m, the second width would be in the range of about 1.05 m to about 0.95 m and still be within 5% of the first width.
[0048] Having described the glass plies, their laminate construction, and their uses, the boroaluminosilicate glass composition will now be described in detail. In an embodiment, the boroaluminosilicate glass composition comprises about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides, primarily Na2O. In certain embodiments, the boroaluminosilicate glass composition has an alkali oxide to Al2O3 ratio of 0.9 to 1.2, particularly about 1.06. Advantageously, the boroaluminosilicate glass composition provides a fusion flow rate of 1000 lb / h to 4500 lb / h (about 454 kg / h to about 2040 kg / h), particularly 2000 lb / h (about 907 kg / h) or more during a fusion forming operation, thereby improving the economics of bulk glass production. This is because a relatively high flow rate reduces the production time of the glass.
[0049] In embodiments, the boroaluminosilicate glass composition includes SiO2 in an amount ranging from about 55 mol% to about 67 mol%. For example, the boroaluminosilicate glass composition may include about 55 mol% to about 67 mol%, about 56 mol% to about 67 mol%, about 57 mol% to about 67 mol%, about 58 mol% to about 67 mol%, about 59 mol% to about 67 mol%, about 60 mol% to about 67 mol%, about 61 mol% to about 67 mol%, about 62 mol% to about 67 mol%, about 63 mol% to about 67 mol%, about 64 mol% to about 67 mol%, about 65 mol% to about 67 mol%, about 66 mol% to about 67 mol%, about 67 mol% to about 67 mol%, about 68 mol% to about 67 mol%, about 69 mol% to about 67 mol%, about 70 mol% to about 67 mol%, about 71 mol% to about 67 mol%, about 72 mol% to about 67 mol%, about 73 mol% to about 67 mol%, about 74 mol% to about 67 mol%, about 75 mol% to about 67 mol%, about 76 mol% to about 67 mol%, about 77 mol% to about 67 mol%, about 78 mol% to about 67 mol%, about 79 mol% to about 67 mol%, about 80 mol% to about 67 mol%, about 81 mol% to about 67 mol%, about 82 mol% to about 67 mol%, about 83 mol% to about 67 mol%, about 84 mol% to about 67 mol%, about 85 mol% to The glass may include SiO2 in an amount ranging from about 55 mol% to about 66 mol%, about 55 mol% to about 65 mol%, about 55 mol% to about 64 mol%, about 55 mol% to about 63 mol%, about 55 mol% to about 62 mol%, about 55 mol% to about 61 mol%, about 55 mol% to about 60 mol%, about 55 mol% to about 59 mol%, about 55 mol% to about 58 mol%, about 55 mol% to about 57 mol%, about 55 mol% to about 56 mol%, or any range or subrange therebetween. In other embodiments, the glass may have less than 55 mol% SiO2, or more than 67 mol% SiO2. Silica content within this range beneficially increases the liquidus viscosity of the glass to facilitate fusion molding while providing favorable chemical and mechanical durability characteristics of the glass.
[0050] In embodiments, the boroaluminosilicate glass composition includes B2O3 in an amount ranging from about 10 mol% to about 13 mol%, particularly from about 11 mol% to about 12 mol%. In various embodiments, the boroaluminosilicate glass composition includes B2O3 in an amount ranging from about 10 mol% to about 13 mol%, from about 10.5 mol% to about 13 mol%, from about 11 mol% to about 13 mol%, from about 11.5 mol% to about 13 mol%, from about 12 mol% to about 13 mol%, from about 12.5 mol% to about 13 mol%, from about 10 mol% to about 12.5 mol%, from about 10 mol% to about 12 mol%, from about 10 mol% to about 11.5 mol%, from about 10 mol% to about 11 mol%, from about 10 mol% to about 10.5 mol%, or any range or sub-range therebetween. In other embodiments, the glass may have less than 10 mol % B2O3, or more than 13 mol % B2O3. Such amounts of B2O3 may provide favorable viscosity characteristics for the glass (e.g., the 10 mol % B2O3 described herein). 11 The glass matrix is then melted and cooled, providing increased connectivity to the glass network and favorable mechanical properties while providing improved thermal stability (e.g., Poise temperature).
[0051] In embodiments, the boroaluminosilicate glass composition includes Al2O3 in an amount ranging from about 11 mol% to about 15 mol%, specifically, from about 12.5 mol% to about 13.5 mol%. In various embodiments, the boroaluminosilicate glass composition includes Al2O3 in an amount in the range from about 11 mol% to about 15 mol%, from about 11 mol% to about 15 mol%, from about 11.5 mol% to about 15 mol%, from about 12 mol% to about 15 mol%, from about 12.5 mol% to about 15 mol%, from about 13 mol% to about 15 mol%, from about 13.5 mol% to about 15 mol%, from about 14 mol% to about 15 mol%, from about 14.5 mol% to about 15 mol%, from about 11 mol% to about 14.5 mol%, from about 11 mol% to about 14 mol%, from about 11 mol% to about 13.5 mol%, from about 11 mol% to about 13 mol%, from about 11 mol% to about 12.5 mol%, from about 11 mol% to about 12 mol%, from about 11 mol% to about 11.5 mol%, or any range or sub-range therebetween. In other embodiments, the boroaluminosilicate glass composition may have less than 11 mol% Al2O3, or more than 15 mol% Al2O3. Such amounts of Al2O3 may increase the liquidus viscosity of the glass and contribute to the structural network.
[0052] In embodiments, the boroaluminosilicate glass composition includes alkali oxides in an amount ranging from about 12 mol% to about 16 mol%. In embodiments, the alkali oxide used in the boroaluminosilicate glass composition is primarily Na2O (e.g., Na2O may be the only alkali oxide or may comprise the majority of the alkali oxide content). In some embodiments, K2O and / or Li2O are also used in the boroaluminosilicate glass composition. In various embodiments, the boroaluminosilicate glass composition comprises alkali oxides in an amount in the range from about 12 mol% to about 16 mol%, about 12.5 mol% to about 16 mol%, about 13 mol% to about 16 mol%, about 13.5 mol% to about 16 mol%, about 14 mol% to about 16 mol%, about 14.5 mol% to about 16 mol%, about 15 mol% to about 16 mol%, about 15.5 mol% to about 16 mol%, about 12 mol% to about 15.5 mol%, about 12 mol% to about 15 mol%, about 12 mol% to about 14.5 mol%, about 12 mol% to about 14 mol%, about 12 mol% to about 13.5 mol%, about 12 mol% to about 13 mol%, about 12 mol% to about 12.5 mol%, or any range or sub-range therebetween. In other embodiments, the glass may have less than 12 mol % alkali oxides, or more than 16 mol % alkali oxides. Such amounts of Na2O may contribute to the viscosity characteristics of the glass.
[0053] The boroaluminosilicate glass compositions may contain up to about 1 mol % Li2O and / or up to about 2 mol % K2O out of 12 mol % to 16 mol % alkali oxides. Li2O and K2O are significantly more expensive as raw materials than Na2O, and one of the advantages of the boroaluminosilicate glass compositions disclosed herein is the high fusion flow rate, which reduces manufacturing costs. Therefore, the inclusion of significant amounts of Li2O and Na2O may offset the savings provided by the high fusion flow rate. The addition of Li2O and K2O is not believed to adversely affect the properties of the disclosed boroaluminosilicate glass compositions, and it is believed that if the cost of these alkali oxides were to decrease, then the limitations of Li2O and K2O in the embodiments to about 1 mol % and about 2 mol % would no longer apply.
[0054] In embodiments, the boroaluminosilicate glass composition may also include P2O5 and / or MgO. In such embodiments, the total amount of such additives is up to about 1 mol %.
[0055] In embodiments, the amount of alkali oxide relative to Al2O3 is in the ratio (Na2O:Al2O3) from about 0.9 to about 1.2, from about 0.95 to about 1.2, from about 1 to about 1.2, from about 1.05 to about 1.2, from about 1.1 to about 1.2, from about 1.15 to about 1.2, from about 0.9 to about 1.15, from about 0.9 to about 1.1, from about 0.9 to about 1.05, from about 0.9 to about 1, from about 0.9 to about 0.95. In certain embodiments, the ratio is about 1.06.
[0056] In embodiments, the glass composition (or glass article formed therefrom) exhibits a liquidus viscosity of at least 20,000 kP and up to 10,000,000 kP. Advantageously, glass compositions having a liquidus viscosity of greater than 1000 kP are less susceptible to baggy warping during fusion drawing. As used herein, the term "liquidus viscosity" refers to the viscosity of molten glass at its liquidus temperature, where the term "liquidus temperature" refers to the temperature at which crystals first appear as the molten glass cools from its melting temperature (or the temperature at which the last crystal melts away as the temperature is increased from room temperature). The liquidus viscosity is determined by the following method. First, the liquidus temperature of the glass is measured according to ASTM C829-81 (2015), entitled "Standard Practice for Measurement of Liquidus Temperature of Glass by the Gradient Furnace Method." The viscosity of the glass at its liquidus temperature is then measured according to ASTM C965-96 (2012), entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point." Advantageously, the high liquidus viscosities associated with the presently disclosed boroaluminosilicate glasses substantially eliminate the risk of devitrification of the glass during manufacture.
[0057] As previously mentioned, the presently disclosed boroaluminosilicate glass compositions are particularly suitable for fusion forming. In many cases, fusion forming is performed with an isopipe made from a material containing zircon. In some cases, the zircon of the isopipe can react with the molten glass to produce undesirable zirconia defects in the final glass product. The reaction between the molten glass and the zircon-containing isopipe is a strong function of temperature, and therefore the "zircon decomposition temperature" can be defined as the temperature above which the reaction of zircon with the molten glass is reasonably expected to result in commercially unacceptable levels of zirconia defects. The zircon decomposition temperature is a function of the composition of the molten glass. Thus, glass compositions that are highly reactive with zircon will have low zircon decomposition temperatures, while more inert glass compositions will have high zircon decomposition temperatures. In one or more embodiments, the presently disclosed boroaluminosilicate glass compositions have a zircon decomposition temperature of at least 1100° C., at least 1125° C., at least 1150° C., at least 1175° C., at least 1200° C., at least 1225° C., at least 1250° C., or at least 1275° C. In one or more embodiments, the presently disclosed boroaluminosilicate glass compositions have a zircon decomposition temperature up to 1300° C. In one or more embodiments, the presently disclosed boroaluminosilicate glass compositions have a zircon decomposition temperature in the range of 1100° C. to 1300° C., particularly in the range of 1150° C. to 1250° C.
[0058] In embodiments, the borosilicate glass composition exhibits a strain point temperature in the range of about 510° C. to about 540° C., about 515° C. to about 540° C., about 520° C. to about 540° C., about 525° C. to about 540° C., about 530° C. to about 540° C., about 535° C. to about 540° C., about 510° C. to about 535° C., about 510° C. to about 530° C., about 510° C. to about 525° C., about 510° C. to about 520° C., about 510° C. to about 515° C., or any range or sub-range therebetween. In embodiments, the strain point temperature is determined using the beam bending viscosity method of ASTM C598-93(2013). In embodiments, the strain point is determined when the viscosity is 10 14.68 It is defined as the temperature at which the force is in poise.
[0059] In embodiments, the borosilicate glass composition exhibits an anneal point temperature in the range of about 560° C. to about 590° C., about 565° C. to about 590° C., about 570° C. to about 590° C., about 575° C. to about 590° C., about 580° C. to about 590° C., about 585° C. to about 590° C., about 560° C. to about 585° C., about 560° C. to about 580° C., about 560° C. to about 575° C., about 560° C. to about 570° C., about 560° C. to about 565° C., or any range or sub-range therebetween. The anneal point is determined using the beam bending viscosity method of ASTM C598-93(2013). In embodiments, the anneal point is determined when the viscosity is 10 13.18 It is defined as the temperature at which the force is in poise.
[0060] In embodiments, the borosilicate glass composition exhibits a softening point temperature in the range from about 800° C. to about 840° C., from about 800° C. to about 835° C., from about 800° C. to about 830° C., from about 800° C. to about 825° C., from about 800° C. to about 820° C., from about 800° C. to about 815° C., from about 800° C. to about 810° C., from about 800° C. to about 805° C., from about 805° C. to about 840° C., from about 810° C. to about 840° C., from about 815° C. to about 840° C., from about 820° C. to about 840° C., from about 825° C. to about 840° C., from about 830° C. to about 840° C., from about 835° C. to about 840° C., or any range or subrange therebetween. The softening point is determined using the Beam Bending Viscosity Method of ASTM C338-93(2003).
[0061] In one or more embodiments, the glass composition or glass article formed therefrom has a viscosity of 2.4 g / cm 3 In an embodiment, the density at 20° C. is less than 2.39 g / cm 3 Below, 2.38g / cm 3 Below, 2.37g / cm 3 Below, 2.36g / cm 3 Below 2.35g / cm 3 Below, 2.34g / cm 3 Below, 2.33g / cm 3 Below, 2.32g / cm 3 or less than 2.31g / cm 3 In an embodiment, the density at 20° C. is at least 2.30 g / cm 3 In an embodiment, the density is determined using the buoyancy method of ASTM C693-93(2013). Conveniently, the density is 2.4 g / cm 3 The density of less than 100 nm is lower than the density of soda lime glass, which is traditionally used in automotive glazing laminates.
[0062] As previously noted, borosilicate glass compositions according to the present disclosure are particularly suitable for fusion forming, particularly with respect to high fusion flow rates. The resulting glass plies can be described as "fusion formed." FIG. 5 illustrates an exemplary embodiment of an apparatus 700 for fusion forming glass plies from boroaluminosilicate glass compositions. The fusion forming apparatus 700 includes an isopipe 702 defined by a trough 704, a first molding surface 706, and a second molding surface 708. The first molding surface 706 and the second molding surface 708 are angled inwardly below the trough 704 and meet at a base 710 of the isopipe 702. The presently disclosed borosilicate glass composition 712 is provided in a molten state to the trough 704, where the borosilicate glass composition 712 overflows the trough 704, forming two streams that flow down the molding surfaces 706, 708. These streams of molten glass meet at base 710 to form a ply of glass 714 that cools and is severed from the flowing streams.
[0063] In an embodiment, the fusion molding apparatus 700 optionally includes a second isopipe 716 having a second trough 718, a third molding surface 720, and a fourth molding surface 722. A glass composition 724 having the same or different composition as the borosilicate glass composition 712 is provided in a molten state to the second trough 718 and overflows the second trough 718. The molten glass composition 724 flows down the third and fourth molding surfaces 720, 722 where it is directed outwardly around the borosilicate glass composition 712. In this manner, the glass composition 724 flows down the first and second molding surfaces 706, 708 outside of the flow of the boroaluminosilicate glass composition 712. The combination of the flow of the boroaluminosilicate glass composition 712 and the flow of the glass composition 724 creates a glass ply 714 having cladding layers 726a, 726b at the base 710 of the isopipe 702. Such cladding layers may mechanically strengthen the glass based on residual stresses that arise based on the different thermal expansion coefficients between the compositions 712, 714, or the cladding layers may be chemically strengthened, such as by ion exchange treatment. The cladding layers 726a, 726b may also impart other characteristics, such as special optical properties, to the thus-formed glass ply 714.
[0064] In one or more embodiments, the boroaluminosilicate glass compositions disclosed herein can have a yield of at least 1000 lb / h (about 454 kg / h), at least 1100 lb / h (about 500 kg / h), at least 1200 lb / h (about 544 kg / h), at least 1300 lb / h (about 590 kg / h), at least 1400 lb / h (about 635 kg / h), at least 1500 lb / h (about 680 kg / h), at least 1600 lb / h (about 726 kg / h), at least 1700 lb / h (about 1800 kg / h), at least 1800 lb / h (about 1900 kg / h), at least 1900 lb / h (about 2000 kg / h), at least 2000 lb / h (about 2100 kg / h), at least 2100 lb / h (about 2200 kg / h), at least 2200 lb / h (about 2300 kg / h), at least 2300 lb / h (about 2400 kg / h), at least 2400 lb / h (about 2500 kg / h), at least 2500 lb / h (about 2600 kg / h), at least 2600 lb / h (about 2700 kg / h), at least 2700 lb / h (about 2800 kg / h), at least 2800 lb / h (about 3000 kg / h), at least 2900 lb / h (about 3100 kg / h), at least 3100 lb / h (about 3200 kg / h), at least 3200 lb / h (about 3300 kg / h), at least 3300 lb / h g / h), at least 1700 lb / h (about 771 kg / h), at least 1800 lb / h (about 817 kg / h), at least 1900 lb / h (about 862 kg / h), at least 2000 lb / h (about 907 kg / h), at least 2100 lb / h (about 953 kg / h), at least 2200 lb / h (about 998 kg / h), at least 2300 lb / h (about 1040 kg / h), at least 2400 lb / h (about 1090 kg / h), at least 2 500 lb / h (approximately 1130 kg / h), at least 2600 lb / h (approximately 1180 kg / h), at least 2700 lb / h (approximately 1230 kg / h), at least 2800 lb / h (approximately 1270 kg / h), at least 2900 lb / h (approximately 1320 kg / h), at least 3000 lb / h (approximately 1360 kg / h), at least 3100 lb / h (approximately 1410 kg / h), at least 3200 lb / h (approximately 1450 kg / h), at least 3300 lb / h (about 1500 kg / h), at least 3400 lb / h (about 1540 kg / h), at least 3500 lb / h (about 1590 kg / h), at least 3600 lb / h (about 1630 kg / h), at least 3700 lb / h (about 1680 kg / h), at least 3800 lb / h (about 1720 kg / h), at least 3900 lb / h (about 1770 kg / h), or at least 4000 lb / h (about 1810 kg / h). In one or more embodiments, the fusion flow rate is up to 4500 lb / h (about 2040 kg / h).In one or more embodiments, the fusion flow rate is in the range of about 1000 lb / h (about 454 kg / h) to about 4500 lb / h (about 2040 kg / h), about 2000 lb / h (about 907 kg / h) to about 3000 lb / h (about 1360 kg / h), particularly about 2200 lb / h (about 998 kg / h) to about 2600 lb / h (about 1180 kg / h), and most preferably about 2300 lb / h (about 1040 kg / h) to about 2500 lb / h (about 1130 kg / h).
[0065] The fusion forming method presents the advantage that, as the two glass streams flowing over the passageway fuse together, none of the exterior surfaces of the resulting glass article come into contact with any part of the apparatus. Thus, the surface properties of the fusion draw formed glass article are not affected by such contact. Specifically, fusion formed boroaluminosilicate glass does not exhibit the draw lines associated with conventional float formed glass. In embodiments, the fusion formed borosilicate glass compositions of the present disclosure exhibit optical distortion of 75 millidiopters or less as measured with an optical distortion detector using transmission optics according to ASTM 1561.
[0066] In addition, one or more embodiments of the glass plies 200 formed from boroaluminosilicate glasses can be strengthened by ion exchange. In the ion exchange process, ions at or near the surface of the glass ply are replaced - i.e., exchanged - with larger ions having the same valence or oxidation state. In those embodiments in which the glass plies are made from the presently disclosed boroaluminosilicate glasses, the ions in the surface layer of the article and the larger ions are selected from the group consisting of Li + , Na + , K + , Rb + , and Cs + Alternatively, the monovalent cations in the surface layer are Ag +etc. In such embodiments, stress is induced by the monovalent ions (i.e., cations) exchanged into the glass plies.
[0067] The ion exchange process is typically carried out by immersing the glass ply in a molten salt bath (or two or more molten salt baths) containing the larger ions to be exchanged for the smaller ions in the glass ply. It should be noted that aqueous salt baths may also be utilized. In addition, the composition of the bath may contain more than one type of larger ion (e.g., Na + and K. + ) or one of the larger ions. Those skilled in the art will recognize that the parameters of the ion exchange process, including but not limited to the bath composition and temperature, immersion time, number of immersions of the glass sheet in the salt bath, use of multiple salt baths, additional steps such as annealing, washing, etc., are generally determined by the composition of the glass sheet (including the structure of the article and any crystalline phases present) and the desired depth of compressive stress (DOC) and compressive stress (CS) of the glass sheet resulting from the strengthening. Exemplary molten bath compositions may include nitrates, sulfates, and chlorides of the larger alkali metal ions. Typical nitrates include KNO3, NaNO3, LiNO3, NaSO4, and combinations thereof. The temperature of the molten salt bath generally ranges from about 380°C to about 450°C, while the immersion time ranges from about 15 minutes to about 100 hours, depending on the thickness of the glass sheet, the temperature of the bath, and the diffusivity of the glass (or monovalent ions). However, temperatures and immersion times different from those described above may also be used.
[0068] According to one or more embodiments, the glass ply 200 may be immersed in a molten salt bath of 100% NaNO3, 100% KNO3, or a combination of NaNO3 and KNO3 having a temperature of about 370° C. to about 480° C. In some embodiments, the glass sheet may be immersed in a molten mixed salt bath including about 5% to about 90% KNO3 and about 10% to about 95% NaNO3. In some embodiments, the glass sheet may be immersed in a first bath and then in a second bath. The first and second baths may have different compositions and / or temperatures. The immersion times in the first and second baths may vary. For example, the immersion in the first bath may be longer than the immersion in the second bath.
[0069] According to one or more embodiments, the glass ply may be immersed in a molten mixed salt bath including NaNO3 and KNO3 (e.g., 49% / 51%, 50% / 50%, 51% / 49%) having a temperature less than about 420° C. (e.g., about 400° C. or about 380° C.) for less than about 5 hours, or even less than about 4 hours.
[0070] The ion exchange conditions can be tailored to increase the gradient, or to provide a "spike" in the stress profile at or near the surface of the resulting glass ply, which would result in a larger surface CS value. This spike can be achieved with a single bath or multiple baths, which may have a single composition or a mixture of compositions due to the specific nature of the glass compositions used in the glass sheets described herein.
[0071] In one or more embodiments in which multiple monovalent ions are exchanged into the glass ply, different monovalent ions may be exchanged to different depths within the glass ply (producing different magnitudes of stress in the glass sheet at different depths), and the resulting relative depths of the stress-producing ions can be determined, thereby producing different characteristics of the stress profile.
[0072] CS is measured using means known in the art, such as by a surface stress meter (FSM) using commercially available equipment such as the FSM-6000 manufactured by Orihara Seisakusho Co., Ltd. (Japan). Surface stress measurements rely on precise measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. SOC is then measured by methods known in the art, such as the fiber method and the four-point bending method, both of which are described in ASTM standard C770-98 (2013), entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," and the bulk cylinder method, the contents of which are incorporated herein in their entirety by reference. As used herein, CS may be the "maximum compressive stress," which is the highest compressive stress value measured within the compressive stress layer. In some embodiments, the maximum compressive stress is located at the surface of the glass sheet. In other embodiments, the maximum compressive stress may occur at some depth below the surface, giving the compressive profile the appearance of a "buried peak."
[0073] The DOC can be measured by FSM or by a Scattered Light Polariscope (SCALP) (such as the SCALP-04 Scattered Light Polariscope available from Glasstress Ltd., Tallinn, Estonia). If the glass plies are chemically strengthened by an ion exchange process, then either the FSM or the SCALP can be used depending on which ions are exchanged into the glass sheets. If the stress in the glass plies is caused by exchanging potassium ions into the glass plies, then the FSM is used to measure the DOC. If the stress is caused by exchanging sodium ions into the glass sheets, then the SCALP is used to measure the DOC. If the stress in the glass plies is caused by exchanging both potassium and sodium ions into the glass, then the DOC is measured by SCALP. Because the exchange depth of the sodium ions is considered to represent the DOC, and the exchange depth of the potassium ions is considered to represent the change in the magnitude of the compressive stress (and not the change in the stress from compressive to tensile); the exchange depth of the potassium ions in such glass plies is measured by the FSM. Central tension or CT is the maximum tensile stress and is measured by SCALP.
[0074] In one or more embodiments, the glass sheet may be strengthened to exhibit a DOC, expressed as a percentage of the thickness T (as described herein) of the glass ply. For example, in one or more embodiments, the DOC may range from about 0.05T to about 0.25T. In some cases, the DOC may range from about 20 μm to about 300 μm. In one or more embodiments, the strengthened glass ply may have a CS (as may be found at the surface or at a depth within the glass sheet) of about 200 MPa or more, about 500 MPa or more, or about 1050 MPa or more. In one or more embodiments, the strengthened glass ply may have a maximum tensile stress or central tension (CT) in the range of about 20 MPa to about 100 MPa. EXAMPLES
[0075] Various embodiments of the presently disclosed boroaluminosilicate glass compositions are provided in the table below.
[0076] [Table 1]
[0077] Examples 1-6 are exemplary glass compositions according to one or more embodiments of the present disclosure. As previously mentioned, the boroaluminosilicate glasses of the present disclosure are made for fusion forming. Generally, fusion forming requires a liquidus viscosity greater than 500 kP and a temperature below 1725° C. where the viscosity is 200 P (T 200P As can be seen from Table 1, the liquidus viscosities of these boroaluminosilicate glass compositions are well above the 500 kP required for fusion molding the glass compositions. In fact, the lowest liquidus viscosity of the six exemplary compositions is greater than 35,000 kP. Furthermore, the T 200P is well below 1725° C., specifically in the range of 1560° C. to 1600° C. Additionally, the boroaluminosilicate glass compositions shown in Table 1 have fusion flow rates in the range of 2300 lb / h (about 1040 kg / h) to 2500 lb / h (about 1130 kg / h), which is higher than other glass compositions used in the thin inner plies of automotive glazing laminates. For example, an alkali aluminosilicate glass composition that can be strengthened by ion exchange (64.85 mol% SiO, 9.06 mol% AlO, 0.93 mol% PO, 16.9 mol% NaO, 2.43 mol% KO, 3.65 mol% MgO, 1.95 mol% ZnO, and 0.22 mol% SnO) has a fusion flow rate of less than 2000 lb / h, specifically about 1992 lb / h. In this regard, the projected cost per square foot of the alkali aluminosilicate glass composition that can be strengthened by ion exchange is about 33% more expensive during fusion molding production.
[0078] Also advantageously, the presently disclosed boroaluminosilicate glass composition has a glass density of 2.4 g / cm 3 Conventional laminates have a density of less than 2.4 g / cm 3 Thus, the disclosed fusion formable boroaluminosilicate glass composition has a density greater than 2.4 g / cm. 3 Less than 2.37 g / cm 3 Offers density-based weight savings (and therefore improved fuel efficiency) of:
[0079] The thermal properties of the resulting glass plies are also improved in terms of the low temperature coefficient of thermal expansion (LTCTE), which is determined by measuring the expansion of the glass between temperatures of 0° C. and 300° C. In embodiments, the LTCTE is 9 ppm / ° C. or less, 8.5 ppm / ° C. or less, 8 ppm / ° C. or less, 7.9 ppm / ° C. or less, particularly 7.6 ppm / ° C. or less, and even 7.4 ppm / ° C. or less. In one or more embodiments, the LTCTE ranges from 7 ppm / ° C. to 9 ppm / ° C. For comparison, the alkali aluminosilicate glass composition that can be strengthened by ion exchange described above has an LTCTE of about 9.95 ppm / ° C. The inclusion of B2O3 in the presently disclosed glass compositions contributes to lowering the LTCTE.
[0080] As mentioned earlier, T 11 The temperature is in a good range for pairing with soda-lime glass or thick fusion-formable borosilicate glass while avoiding optical distortion. The ion-exchange-strengthenable alkali aluminosilicate glass compositions described above have a lower T of about 626° C. 11 The glass has a temperature that is relatively close to that of soda-lime glass or fusion-formable borosilicate glass, which is in the range of about 600° C. to about 615° C.
[0081] Furthermore, due to the inclusion of greater than 10 mole percent of both Al2O3 and B2O3, the inventors believe that plies made from the glass compositions disclosed herein will exhibit improved scratch and indentation resistance.
[0082] Table 2 below provides an example of the ion exchange treatment of Example 3, showing that the disclosed boroaluminosilicate glass composition can be strengthened by ion exchange. The refractive index of the glass was 1.496 and the stress optical coefficient (SOC) was 36.74. This stress optical coefficient was used in determining the compressive stress (CS) and depth of compression (DOC) as described above.
[0083] [Table 2]
[0084] As can be seen from Table 2, the boroaluminosilicate glass compositions were ion-exchanged in 100% KNO3 at 430°C for 4, 9, and 16 hours. After 4 hours of treatment, the specimens of Example 3 had a surface compressive stress of about 600 MPa and a compression depth of 30 μm or more. After 9 hours of treatment, the specimens of Example 3 had a surface compressive stress of less than 550 MPa and a compression depth that increased to 45 μm or more. After 16 hours of treatment, the specimens of Example 3 had a surface compressive stress of about 500 MPa and a compression depth that increased to 60 μm or more.
[0085] In an embodiment, the laminate 300, 400 (or as glass ply 200) described herein may be used in a system 800 that also includes a sensor 810, as shown in FIG. 6. In an embodiment, the laminate 300, 400 is made to be transparent to electromagnetic radiation in the visible spectrum and wavelengths above 1500 nm (e.g., short wave infrared). Signals carried by electromagnetic radiation in these ranges can be transmitted through the laminate 300, 400. FIG. 6 shows a sensor 810 receiving an input signal 820 and transmitting a transmission signal 830 through the laminate 300, 400. For example, in one or more embodiments, the laminate 300, 400 is included as a glazing 130 in a vehicle 100 as shown in FIG. 1. In such an embodiment, the sensor 810 is located within the interior of the vehicle 100. In this manner, signals 820, 830 can be transmitted to and from the vehicle 100. In one or more embodiments, the signals 820, 830 have peak wavelengths in the visible light (about 400 nm to about 750 nm) or shortwave infrared spectrum (1500 nm or greater). In embodiments, such signals facilitate autonomous or semi-autonomous vehicle operation, public road tolling, communications, traffic monitoring and regulation, and vehicle-to-vehicle communications, among other possibilities. One example of a sensor 810 that can be utilized in the system 800 is a LiDAR that utilizes either or both visible light and shortwave infrared radiation. In embodiments of the laminate 300, 400 that include an IRR coating, the IRR coating may be removed from the ply applied in the area where the sensor 810 is designed to transmit and receive signals through the laminate 300, 400. The glass compositions described herein may also find use as protective window covers for LiDAR systems (as a single ply or laminate) located on the exterior of a vehicle.
[0086] The embodiments of the present disclosure will be further understood in view of the following aspects: Embodiment (1) is a glass composition comprising about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides, wherein the viscosity of the borosilicate glass composition is about 100% to about 100% at about 630° C. to about 650° C. 11 For a glass composition having a temperature P.
[0087] The embodiment (2) relates to a glass composition according to the embodiment (1) comprising about 11 mol % to about 12 mol % B2O3.
[0088] The embodiment (3) relates to a glass composition according to the embodiment (1) or (2), comprising about 12.5 mol % to about 13.5 mol % Al2O3.
[0089] An embodiment (4) relates to a glass composition according to any one of the embodiments (1) to (3), in which the alkali oxide includes at least one of Li2O, Na2O, or K2O.
[0090] An embodiment (5) includes the glass composition according to embodiment (4) including up to 1 mol % LiO.
[0091] The embodiment (6) relates to the glass composition according to the embodiments (4)-(5), comprising at most 2 mol % K2O.
[0092] An embodiment (7) relates to a glass composition according to any one of the embodiments (1) to (3), in which the alkali oxide comprises Na2O.
[0093] An embodiment (8) relates to a glass composition according to any one of the embodiments (1) to (7), wherein the ratio of alkali oxide to Al2O3 is in the range of about 0.9 to about 1.2.
[0094] Aspect (9) relates to a glass composition according to any one of aspects (1) to (8), comprising one or both of P2O5 and MgO, the amount of P2O5 and MgO being up to 1 mol %.
[0095] An embodiment (10) relates to a glass composition according to any one of embodiments (1) to (9), having a liquidus viscosity in the range of 20,000 kP to 10,000,000 kP.
[0096] An embodiment (11) relates to a glass composition according to any of embodiments (1) to (10) having a fusion flow rate of 1000 lb / h to 4500 lb / h (about 454 kg / h to about 2040 kg / h).
[0097] The embodiment (12) is at least 2.3 g / cm 3 And 2.4g / cm 3 The present invention relates to a glass composition according to any one of aspects (1) to (11), having a density of less than 1000 nm.
[0098] An embodiment (13) relates to a glass composition according to any one of embodiments (1) to (12), having a thermal expansion coefficient in the range of 7 ppm / °C to 9 ppm / °C.
[0099] An embodiment (14) relates to a glass composition according to any one of the embodiments (1) to (13), having a zircon decomposition temperature in the range of 1100°C to 1300°C.
[0100] Embodiment (15) relates to a laminate comprising a first glass ply made from a glass composition according to any of embodiments (1)-(14), a second glass ply made from a second glass composition, and an interlayer bonding the first glass ply to the second glass ply.
[0101] Embodiment (16) relates to the laminate of embodiment (15), wherein the second ply of glass is thicker than the first ply of glass.
[0102] Embodiment (17) relates to the laminate of any of embodiments (15) to (16), wherein the first glass ply has a first major surface and a second major surface opposite the first major surface, and a thickness between the first major surface and the second major surface, the thickness being 0.1 mm to 2 mm.
[0103] An embodiment (18) relates to a laminate according to embodiment (17), having a thickness of about 0.3 mm to about 1.1 mm.
[0104] Embodiment (19) relates to a vehicle comprising a vehicle body defining an interior of the vehicle and at least one opening, and an automotive glazing comprising a laminate of any one of embodiments (15)-(18) disposed within the at least one opening, with a first glass ply disposed facing the interior of the vehicle and a second glass ply facing the exterior of the vehicle.
[0105] An embodiment (20) relates to the vehicle of embodiment (19), wherein the automotive glazing is at least one of a side window, a windshield, a rear window, a window, or a sunroof.
[0106] Embodiment (21) relates to a method of forming a glass ply, the method including overflowing at least two streams of a glass composition from a trough in an isopipe, the streams including about 55 mol % to about 67 mol % SiO, about 10 mol % to about 13 mol % B0, about 11 mol % to about 15 mol % Al0, and about 12 mol % to about 16 mol % alkali oxides, and fusing the at least two streams of glass composition at a base of the isopipe to form a glass ply.
[0107]
[0023] Embodiment (22) relates to the method of embodiment (21), wherein the glass composition flows at a rate of 1000 lb / h to 4500 lb / h (about 454 kg / h to about 2040 kg / h) during the overflowing and fusing steps.
[0108]
[0023] Example (23) relates to the method of Example (21) or Example (22), wherein the glass composition has a liquidus viscosity of 20,000 kP to 10,000,000 kP.
[0109] An embodiment (24) relates to the method according to any of the embodiments (21) to (23), wherein the glass composition comprises about 11 mol % to about 12 mol % B2O3.
[0110] An embodiment (25) relates to the method according to any of the embodiments (21) to (24), wherein the glass composition comprises about 12.5 mol % to about 13.5 mol % Al2O3.
[0111] An embodiment (26) relates to the method according to any of the embodiments (21) to (25), wherein the alkali oxide comprises at least one of Li2O, Na2O, or K2O.
[0112] Example (27) relates to the method of example (26), wherein the alkali oxide comprises up to 1 mol % LiO.
[0113] Example (28) relates to the method of example (26) or example (27), wherein the alkali oxide comprises up to 2 mol% K2O.
[0114] An embodiment (29) relates to the process according to any of the embodiments (21) to (25), wherein the alkali oxide consists of Na2O.
[0115] An embodiment (30) relates to the process according to any of the embodiments (21) to (29), wherein the ratio of alkali oxide to Al2O3 is in the range of about 0.9 to about 1.2.
[0116] An embodiment (31) relates to the method according to any of the embodiments (21) to (30), wherein the glass composition comprises one or both of P2O5 and MgO, the amount of P2O5 and MgO being up to 1 mol %.
[0117] An embodiment (32) relates to the method according to any one of the embodiments (21) to (31), wherein the glass composition has a zircon decomposition temperature of at least 1100° C.
[0118] In a third aspect, the method includes placing a laminate including a first ply of glass and a second ply of glass on a bending ring including an open interior, the first ply of glass having a viscosity of 10 11 The second ply of glass has a first temperature of 10 poise and the second ply of glass has a viscosity of 10 11heating the laminate to a temperature at which the laminate sags into the open interior of a bending ring; and wherein the first glass ply is made from a first glass composition comprising about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides.
[0119]
[0023] Embodiment (34) relates to the method of embodiment (33), wherein the second ply of glass is thicker than the first ply of glass and the first temperature is greater than the second temperature.
[0120] In an embodiment (35), the first glass composition is a glass having a viscosity of about 10. 11 The method of embodiment (33) or embodiment (34), wherein the temperature is poise.
[0121] In an embodiment (36), the second glass composition is a glass having a viscosity of about 10. 11 The method according to any one of embodiments (33) to (35), wherein the temperature is poise.
[0122] An embodiment (37) relates to the method of any of embodiments (33)-(36), wherein the first ply of glass has a thickness less than 2 mm and the second ply of glass has a thickness of 2 mm or greater.
[0123] Example (38) relates to the method of any of Examples (33)-(37), wherein the first glass composition comprises about 11 mol % to about 12 mol % B2O3.
[0124] Example (39) relates to the method of any of Examples (33)-(38), wherein the first glass composition comprises about 12.5 mol % to about 13.5 mol % Al2O3.
[0125] An embodiment (40) relates to the method of any of the embodiments (33) to (39), wherein the alkali oxide comprises at least one of Li2O, Na2O, or K2O.
[0126] Example (41) relates to the method of example (40), wherein the alkali oxide comprises up to 1 mol% LiO.
[0127] Example (42) relates to the method of example (40) or example (41), wherein the alkali oxide comprises up to 2 mol% K2O.
[0128] An embodiment (43) relates to the process of any one of the embodiments (33) to (39), wherein the alkali oxide comprises Na2O.
[0129] Example (44) relates to the process of any of Examples (33)-(43), wherein the ratio of alkali oxide to Al2O3 is in the range of about 0.9 to about 1.2.
[0130] Example (45) relates to the method of any of Examples (33)-(43), wherein the second glass composition comprises a soda-lime-silicate glass composition.
[0131]
[0036] Example (46) relates to the method of any of Examples (33)-(45), wherein the second glass composition comprises a borosilicate glass composition and the second ply of glass is fusion formed to a thickness of 3 mm or greater.
[0132] Example (47) relates to the method of example (46), wherein the borosilicate glass composition comprises 74 mol% to 80 mol% SiO, 2.5 mol% to 5 mol% AlO, 11.5 mol% to 14.5 mol% BO, 4.5 mol% to 8 mol% NaO, 0.5 mol% to 3 mol% KO, 0.5 mol% to 2.5 mol% MgO, and 0 mol% to 4 mol% CaO.
[0133] Unless otherwise expressly stated, it is in no way intended that any method described herein be construed as requiring that its steps be performed in a particular order. Thus, unless a method claim actually recites the order in which its steps should be followed, or unless the claim or description is otherwise specifically stated to be limited to a particular order, no particular order is in any way intended to be implied. In addition, as used herein, nouns are intended to include one or more components or elements, and are not intended to be construed as meaning just one.
[0134] It will be apparent to those skilled in the art that various modifications and changes can be made without departing from the spirit or scope of the disclosed embodiments. Since modifications, combinations, subcombinations and modifications of the disclosed embodiments incorporating the spirit and substance of the embodiments will occur to those skilled in the art, the disclosed embodiments should be construed as including all within the scope of the appended claims and equivalents thereof.
[0135] Preferred embodiments of the present invention will be described below in detail.
[0136] EMBODIMENT 1 about 55 mol % to about 67 mol % SiO2; about 10 mol % to about 13 mol % B2O3; about 11 mol % to about 15 mol % Al2O3, and about 12 mol % to about 16 mol % of an alkali oxide; A glass composition comprising: The viscosity of the borosilicate glass composition is about 10 at about 630° C. to about 650° C. 11 A glass composition having a temperature P.
[0137] EMBODIMENT 2 2. The glass composition of embodiment 1 comprising about 11 mol% to about 12 mol% B2O3.
[0138] EMBODIMENT 3 3. The glass composition of embodiment 1 or 2, comprising about 12.5 mol % to about 13.5 mol % Al2O3.
[0139] EMBODIMENT 4 4. The glass composition according to any one of claims 1 to 3, wherein the alkali oxide comprises at least one of Li2O, Na2O, or K2O.
[0140] EMBODIMENT 5 5. The glass composition of embodiment 4 comprising up to 1 mol% LiO.
[0141] EMBODIMENT 6 6. The glass composition according to claim 4 or 5, comprising up to 2 mol % K2O.
[0142] EMBODIMENT 7 4. A glass composition according to any one of claims 1 to 3, wherein the alkali oxide consists of Na2O.
[0143] EMBODIMENT 8 8. The glass composition according to any one of the preceding claims, wherein the ratio of alkali oxides to Al2O3 is in the range of about 0.9 to about 1.2.
[0144] EMBODIMENT 9 9. The glass composition according to any one of the preceding claims, comprising one or both of P2O5 and MgO, the amount of P2O5 and MgO being up to 1 mol%.
[0145] EMBODIMENT 10 10. The glass composition according to any one of the preceding claims, having a liquidus viscosity in the range of 20,000 kP to 10,000,000 kP.
[0146] EMBODIMENT 11 11. The glass composition of any of the preceding claims having a fusion flow rate of 1000 lb / h to 4500 lb / h (about 454 kg / h to about 2040 kg / h).
[0147] EMBODIMENT 12 At least 2.3g / cm 3 And 2.4g / cm 3 12. The glass composition according to any one of claims 1 to 11, having a density of less than 1000 nm.
[0148] EMBODIMENT 13 13. The glass composition according to any of the preceding claims, having a thermal expansion coefficient in the range of 7 ppm / °C to 9 ppm / °C.
[0149] EMBODIMENT 14 14. The glass composition according to any one of the preceding claims, having a zircon decomposition temperature in the range of 1100°C to 1300°C.
[0150] EMBODIMENT 15 A first glass ply made from the glass composition according to any one of claims 1 to 14. a second ply of glass made from a second glass composition; and an interlayer bonding the first ply of glass to the second ply of glass; A laminate comprising:
[0151] EMBODIMENT 16 16. The laminate of claim 15, wherein the second ply of glass is thicker than the first ply of glass.
[0152] EMBODIMENT 17 17. The laminate of claim 15 or 16, wherein the first glass ply has a first major surface and a second major surface opposite the first major surface, and a thickness between the first major surface and the second major surface, the thickness being 0.1 mm to 2 mm.
[0153] EMBODIMENT 18 18. The laminate of embodiment 17, wherein the thickness is from about 0.3 mm to about 1.1 mm.
[0154] EMBODIMENT 19 In the vehicle, a vehicle body defining an interior of the vehicle and at least one opening; 19. An automotive glazing comprising a laminate according to any one of claims 15 to 18 disposed within the at least one opening; Equipped with The vehicle, wherein the first ply of glass is positioned to face an interior of the vehicle, and the second ply of glass faces an exterior of the vehicle.
[0155] EMBODIMENT 20 20. The vehicle of embodiment 19, wherein the automotive glazing is at least one of a side window, a windshield, a rear window, a window, or a sunroof.
[0156] EMBODIMENT 21 1. A method of forming a glass ply, comprising: overflowing at least two streams of a glass composition comprising about 55 mol % to about 67 mol % SiO, about 10 mol % to about 13 mol % B0, about 11 mol % to about 15 mol % Al0, and about 12 mol % to about 16 mol % alkali oxides from a trough in the isopipe; fusing at least two streams of the glass composition at a root of the isopipe to form the glass ply; The method includes:
[0157] EMBODIMENT 22 22. The method of claim 21, wherein the glass composition flows at a rate of 1000 lb / h to 4500 lb / h (about 454 kg / h to about 2040 kg / h) during the overflowing and fusing steps.
[0158] EMBODIMENT 23 23. The method of claim 21 or 22, wherein the glass composition has a liquidus viscosity of 20,000 kP to 10,000,000 kP.
[0159] EMBODIMENT 24 24. The method of any one of claims 21 to 23, wherein the glass composition comprises about 11 mol% to about 12 mol% B2O3.
[0160] EMBODIMENT 25 25. The method of any one of claims 21 to 24, wherein the glass composition comprises about 12.5 mol% to about 13.5 mol% Al2O3.
[0161] EMBODIMENT 26 26. The method of any one of claims 21 to 25, wherein the alkali oxide comprises at least one of Li2O, Na2O, or K2O.
[0162] EMBODIMENT 27 27. The method of embodiment 26, wherein the alkali oxide comprises up to 1 mol% LiO.
[0163] EMBODIMENT 28 28. The method of embodiment 26 or 27, wherein the alkali oxide comprises up to 2 mol% K2O.
[0164] EMBODIMENT 29 26. The method of any one of claims 21 to 25, wherein the alkali oxide comprises Na2O.
[0165] EMBODIMENT 30 30. The method of any one of embodiments 21 to 29, wherein the ratio of alkali oxide to Al2O3 is in the range of about 0.9 to about 1.2.
[0166] EMBODIMENT 31 31. The method of any one of claims 21 to 30, wherein the glass composition comprises one or both of P2O5 and MgO, the amount of P2O5 and MgO being up to 1 mol%.
[0167] EMBODIMENT 32 32. The method of any one of claims 21 to 31, wherein the glass composition has a zircon decomposition temperature of at least 1100°C.
[0168] EMBODIMENT 33 In the method, placing a laminate including a first ply of glass and a second ply of glass on a bending ring including an open interior, the first ply of glass having a viscosity of 10 11 The second ply of glass has a first temperature of 10 poise and the second ply of glass has a viscosity of 10 11 a second temperature that is poise, the first temperature being different from the second temperature; heating the laminate to a temperature at which the laminate hangs into the open interior of the bending ring; Including, The first glass ply is made from a first glass composition comprising about 55 mol% to about 67 mol% SiO2, about 10 mol% to about 13 mol% B2O3, about 11 mol% to about 15 mol% Al2O3, and about 12 mol% to about 16 mol% alkali oxides.
[0169] EMBODIMENT 34 34. The method of claim 33, wherein the second ply of glass is thicker than the first ply of glass and the first temperature is greater than the second temperature.
[0170] EMBODIMENT 35 The first glass composition is heated to about 630° C. to about 650° C., and the viscosity of the first glass composition is about 10 11 35. The method of embodiment 33 or 34, having a temperature that is poise.
[0171] EMBODIMENT 36 The second glass composition is heated to about 600° C. to about 615° C., and the viscosity of the second glass composition is about 10 11 36. The method of any one of embodiments 33 to 35, having a temperature that is poise.
[0172] EMBODIMENT 37 37. The method of any one of claims 33 to 36, wherein the first ply of glass has a thickness of less than 2 mm and the second ply of glass has a thickness of 2 mm or more.
[0173] EMBODIMENT 38 38. The method of any one of claims 33 to 37, wherein the first glass composition comprises about 11 mol% to about 12 mol% B2O3.
[0174] EMBODIMENT 39 39. The method of any one of claims 33 to 38, wherein the first glass composition comprises about 12.5 mol% to about 13.5 mol% Al2O3.
[0175] EMBODIMENT 40 40. The method of any one of embodiments 33 to 39, wherein the alkali oxide comprises at least one of Li2O, Na2O, or K2O.
[0176] EMBODIMENT 41 41. The method of embodiment 40, wherein the alkali oxide comprises up to 1 mol% LiO.
[0177] EMBODIMENT 42 42. The method of embodiment 40 or 41, wherein the alkali oxide comprises up to 2 mol% K2O.
[0178] EMBODIMENT 43 40. The method of any one of embodiments 33 to 39, wherein the alkali oxide comprises Na2O.
[0179] EMBODIMENT 44 44. The method of any one of embodiments 33 to 43, wherein the ratio of alkali oxide to Al2O3 is in the range of about 0.9 to about 1.2.
[0180] EMBODIMENT 45 44. The method of any one of claims 33 to 43, wherein the second glass composition comprises a soda-lime-silicate glass composition.
[0181] EMBODIMENT 46 46. The method of any one of claims 33 to 45, wherein the second glass composition comprises a borosilicate glass composition and the second ply of glass is fusion formed with a thickness of 3 mm or more.
[0182] EMBODIMENT 47 47. The method of claim 46, wherein the borosilicate glass composition comprises 74 mol% to 80 mol% SiO, 2.5 mol% to 5 mol% AlO, 11.5 mol% to 14.5 mol% BO, 4.5 mol% to 8 mol% NaO, 0.5 mol% to 3 mol% KO, 0.5 mol% to 2.5 mol% MgO, and 0 mol% to 4 mol% CaO. [Explanation of symbols]
[0183] 100 vehicles 110 Body 120 At least one opening 130 Automotive flat glass 200 Glass ply 202 First main surface 204 Second main surface 206, 336 minor side 210 First Thickness 300 Laminates, laminate structures 310 First glass ply 320 Second Glass Ply 330 Middle Class 332 Third Principal Surface 334 Fourth Principal Surface 340 Second Thickness 400 curved glass laminate 410 First Curvature Depth 420 Second Curvature Depth 700 Fusion Molding Machine 704 Gutter 706 First molding surface 708 Second molding surface 710 base 712 Borosilicate glass composition 714 Glass ply 716 Second Isopipe 718 Second Gutter 720 Third molding surface 722 Fourth molding surface 724 Glass composition 726a, 726b Cladding layer 800 Systems 810 Sensors 820 Input Signal 830 Transmitted Signal
Claims
1. About 55 mol % to about 67 mol % SiO 2 , About 10 mol % to about 13 mol % B 2 O 3 , About 11 mol % to about 15 mol % Al 2 O 3 , and about 12 mol % to about 16 mol % alkali oxide; A glass composition comprising: The viscosity of the glass composition is about 10. 11 A glass composition having a temperature P.
2. About 11 mol % to about 12 mol % B 2 O 3 , About 12.5 mol % to about 13.5 mol % Al 2 O 3 , Up to 1 mol% Li 2 O, and Up to 2 mol% K 2 O. The glass composition of claim 1 , comprising:
3. The alkali oxide is Na 2 O, and alkali oxide vs. Al 2 O 3 The glass composition of claim 1 or 2, wherein the ratio of is in the range of about 0.9 to about 1.
2.
4. P 2 O 5 and MgO, 2 O 5 3. The method of claim 1 or 2, wherein the amount of MgO is at most 1 mol %.
5. A liquidus viscosity in the range of 20,000 kP to 10,000,000 kP; A fusion flow rate of 1000 lb / h to 4500 lb / h (about 454 kg / h to about 2040 kg / h); At least 2.3 g / cm 3 And 2.4 g / cm 3 Density less than A coefficient of thermal expansion in the range of 7 ppm / °C to 9 ppm / °C, and Zircon decomposition temperature in the range of 1100°C to 1300°C; The method according to claim 1 or 2, comprising:
6. In the method, placing a laminate including a first ply of glass and a second ply of glass on a bending ring including an open interior, the first ply of glass having a viscosity of 10 11 The second ply of glass has a first temperature of 10 poise and the second ply of glass has a viscosity of 10 11 a second temperature that is poise, the first temperature being different from the second temperature; heating the laminate to a temperature at which the laminate hangs into the open interior of the bending ring; Including, The first ply of glass has about 55 mol % to about 67 mol % SiO 2 , about 10 mol % to about 13 mol % B 2 O 3 , about 11 mol % to about 15 mol % Al 2 O 3 and about 12 mol % to about 16 mol % alkali oxide.
7. The second glass ply is thicker than the first glass ply, the first temperature is higher than the second temperature, the first glass ply has a thickness of less than 2 mm, the second glass ply has a thickness of 2 mm or more, and the first glass composition is a glass composition having a viscosity of 10 to 150° C. at about 630° C. to about 650° C. 11 The second glass composition has a temperature of about 600° C. to about 615° C., and the viscosity of the second glass composition is about 10 11 7. The method of claim 6 having a temperature that is poise.
8. The first glass composition comprises about 11 mol % to about 12 mol % B. 2 O 3 and the first glass composition comprises about 12.5 mol % to about 13.5 mol % Al. 2 O 3 and the alkali oxide contains up to 1 mol % Li. 2 O, and the alkali oxide contains up to 2 mol % K 2 The method of claim 6 or 7, further comprising:
9. The method of claim 6 or 7, wherein the second glass composition comprises a borosilicate glass composition and the second ply of glass is fusion formed to a thickness of 3 mm or greater.
10. The borosilicate glass composition is 74 mol % to 80 mol % SiO 2 , 2.5 mol % to 5 mol % Al 2 O 3 , 11.5 mol % to 14.5 mol % B 2 O 3 , 4.5 mol% to 8 mol% Na 2 O, 0.5 mol % to 3 mol % K 2 10. The method of claim 9, comprising: 0.5 to 2.5 mol% MgO; and 0 to 4 mol% CaO.